Structure modification of an antibiotic: by engineering the fusaricidin bio-synthetase A in Paenibacillus polymyxa - Li, Yunlong; Chen, Sanfeng (Frontiers in Microbiology, 2023)
Fusaricidin, a lipopeptide antibiotic, is specifically produced by Paenibacillus polymyxa strains, which could strongly inhibit Fusarium species fungi. Fusaricidin bio-synthetase A (FusA) is composed of six modules and is essential for synthesizing the peptide moiety of fusaricidin. In this study, we confirmed the FusA of Paenibacillus polymyxa strain WLY78 involve in producing Fusaricidin LI-F07a. We constructed six engineered strains by deletion of each module within FusA from the genome of strain WLY78, respectively. One of engineered strains is able to produce a novel compound which exhibits better antifungal activity than that of fusaricidin LI-F07a. This new compound, known as fusaricidin [ΔAla 6 ] LI-F07a, has a molecular weight of 858. Our findings reveal that it exhibits a remarkable 1-fold increase in antifungal acitvity compared to previous fusaricidin and the fermentation yield reaches ~55 mg/L. This research holds promising implications for plant protection against infections caused by Fusarium and Botrytis pathogen infection.